The long-range effect induced by untying hydrogen bonds for single cell test using SECM. (20th July 2016) - Zheng, Qing; Yang, Yifan; Yan, Yuanyuan; Yu, Yu; Liu, Yao; Gao, Wenyu; Ding, Kejian; Shao, Huibo
Graphical abstract: Highlights: The enhanced positive feedback current of SECM is observed at a large tip-substrate separation in the case of a 3-MPA SAM. The long-range effect is resulting from concentration increment of redox species by untying the hydrogen bonds beforehand formed between the tip redox species and the 3-MPA SAM. The long-range effect is applied to the single cell test using SECM which is beneficial for cell tests without affecting the natural metabolic pathway and cell morphology. Abstract: The enhanced positive feedback current of scanning electrochemical microscopy (SECM) is observed at a large separation between the tip and the substrate surface in the case of a 3-mercaptopropionic acid (3-MPA) self-assembled monolayer (SAM). The effect that induces the large separation (named the long-range effect) is confirmed by SECM and quantitatively studied by electrochemical quartz crystal microbalance (EQCM). A key finding is that the long-range effect results from untying hydrogen bonds beforehand formed between the hydroxyl group of tip redox species and the carboxyl group of 3-MPA SAM. It is found that the long-range effect is increased with the packing density of the 3-MPA SAM. On the basis of these findings, the long-range effect is applied to the nondestructive test of living cells using SECM.